A course in monetary economics : sequential trade, money, and uncertainty - Eden, Benjamin (Malden, MA : Blackwell Pub., 2005)
Monetary Economics and Sequential Trade is an insightful introduction to the advanced topics in monetary economics. Accessible to students who have mastered the diagrammatic tools of economics, it discusses real issues with a variety of modeling alternatives, allowing for a direct comparison of the implications of the different models. The exposition is clear and logical, providing a solid foundation in monetary theory and the techniques of economic modeling. The text is rooted in the author's years of teaching and research, and will be highly suitable for monetary economics courses in both the upper-level undergraduate and graduate levels.
&#x000A
Overview -- Money in the utility function -- The welfare cost of inflation in a growing economy -- Government -- More explicit models of money -- Optimal fiscal and monetary policy -- Money and the business cycle: does money matter? -- Sticky prices in a demand-satisfying model -- Sticky prices with optimal quantity choices -- Flexible prices -- Part 2: An introduction to the economics of uncertainty -- Preliminaries -- Does insurance require risk aversion? -- Asset prices and the Lucas' "tree model" -- Part 3: An introduction to uncertain and sequential trade (UST) -- Real models -- A monetary model -- Limited participation, sticky prices, and UST: a comparison -- Inventories and business cycle -- Money and credit in the business cycle -- Evidence from micro data -- The Friedman rule in UST model -- Sequential international trade -- Endogenous information and externalities -- Search and contracts.
rpm 09/05/13
Loans
Keywords: Uncertainty -- Mathematical models; Money -- Mathematical models